EFFECT OF USING THE LEMONGRASS (Cimbopogon citratus) TO SMOKED EEL (Monopterus albus) PROCESSING QUALITY - Viki Buana Satria; Dewita Buchari; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study was aimed to determine the effect of using the lemongrass on organoleptic quality of smoked eel. 4 kg of fresh eel and lemongrass obtained from one of market in Pekanbaru processed into smoked eel. The treatment of this study was using the different concentration of lemongrass (0%, 10%, 20% and 30%) from fresh eel to determine the quality of smoked eel. The result showed that the lemongrass with concentration 30% was the best treatment and most favorable by consumer with appearance 7.41, texture 7.79, odor 7.32, flavor 7.07, moisture content 14.04%, ash content 22.30%, protein content 49.75% and fat content 2.75%.Keywords: Smoked eel, Lemongrass, Processing